IMPROVING READING COMPREHENSION BY USING JIGSAW STRATEGY AT STKIP PAHLAWAN TUANKU TAMBUSAI - Lusi Marleni (Journal of English Language and Education, 2017)
This research was taken based on the students problem to memorize, apply, understand and comprehend the English texts. The students also cannot interpret the authors message. The purpose of this research is to improve the students reading comprehension of the first semester of English Study Program of STKIP Pahlawan Tuanku Tambusai. The participants of this research are the first semester students of English Study Program of STKIP Pahlawan Tuanku Tambusai. The classroom action research was done in four steps plan, action, observation, and reflection in three cycles. This study shows that Jigsaw Strategy can improve the students reading comprehension. Based on the data, the percentage improve significantly from the first to the third test. The first test, the percentage was 18.92%, then at the second test was 27.03% and at the third test was 45.21%. At the second and third cycles, there was no students could achieved this level, but the percentage directly increase to 35.14%. Therefore, the students reading comprehension can be improved through Jigsaw Strategy.`